ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK (Studi Empiris Pada Wajib Pajak Orang Pribadi Yang Melakukan Kegiatan Usaha Di Kota Semarang) - Rahayu Hana Puspita Rusli; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
This research aims to analyze the factors that affect individual taxpayers in meeting their to pay taxes obligation. This research consists of four independent variables and one dependent variable. Independent variables in this research are tax consciousness, tax penalties, tax authorities attitude, and knowledge and understanding of tax regulations.  While the dependent variable in this research is taxpayer’s compliance.This study uses quantitative research methods, where the data obtained from questionnaires with  Random  Sampling technique. Respondents were sampled in this study are an individual taxpayer who carries on business in the city of Semarang. Analysis of research data using multiple linear regression analysis with SPSS 20.00 program for Windows.Based on the results of the analysis has been done, this research shows that the tax consciousness, tax penalties, tax authorities attitude, and knowledge and understanding of tax regulations have a positive and significant impact on  taxpayer’s compliance.